Kajian Mendalam tentang Konsep dan Implikasi Sosial Syirik dalam Konteks Keagamaan - Abd. Muis, Andi; Rahma, Alia; Sri Wulan Dari, Sri; Haeriah, Nur (Universitas Nahdlatul Ulama Sunan Giri, 2023)
Shirk is an act that assosciates or duplicates something other than Allah . Shirk is the greatest sin and injustice. Shirk is divided into two types, namely shirk al-akbar (large shirk) and shirk al-asghar (small shirk). Shirk al-Akbar is the most serious and major form of shirk in Islamic teachings because it excludes the perpetrators from Islam, such as worshiping idols, asking for help from the dead, or assuming there is someone in authority other than Allah. Shirk al-ashgar is a milder form of shirk than shirk al-akbar because it does not expel the perpetrator from Islam, but reduces his rewards and deeds, such as vows other than Allah, riya, or takabur. Shirk is caused by various factors, such as liking, love, faith, fear, desire or taqlid (following along). Shirk has a very bad impact on humans, reducing rewards, preventing entry to heaven, causing punishment, and detouring from the path of Allah. Shirk must be avoided by increasing knowledge, faith, sincerity, , making dhikr, always remembering Allah, and staying away from all Allah's prohibitions.